PTH-036 End Of Life Care In Liver Disease. (9th June 2014) - Chiplen, F; Lawton, S; Linklater, G; Salunke, S; Cogdell, L; Fraser, A; Vijayan, B
Abstract : Introduction: Living and Dying Well: a national action plan for palliative and end of life care for Scotland calls for the identification, assessment, monitoring and care planning for palliative patients, irrespective of diagnosis or location. The primary aim of this project was to audit the assessment, care planning and recording of palliative status in the Gastroenterology Department in Aberdeen. Methods: Patients who died of chronic liver disease between July 2011 and May 2012 were identified using a retrospective notes review approach. A data capture sheet was devised in consultation with Senior Medical staff from the Gastroenterology and Palliative Medicine Departments. Results: Twenty patients were identified. The audit standard of 90% was met in the following: dying recognised and recorded in the medical notes; dying recognised and recorded in the nursing notes; DNACPR in place; record of discussion with the family and agreed plan with family; anticipatory prescribing. The 90% standard was not met for medication review, discontinuing unnecessary medication or non-essential monitoring/ interventions. None of the prognostic tools examined (MELD, Child Pugh, MI, GAHS) showed high sensitivity for recognising poor prognosis in this patient group. Almost all the patients who died in the acute sector had been admitted as unscheduled emergencies. None had any evidence of pre-admission advance care planning. Conclusion: This audit demonstrated a high standard of end-of-life care in the GI unit despite the difficulties identified in prognosticating in this patient group. There is a need to further explore whether advance care planning is possible and practicable for patients with chronic liver disease. Reference: Scottish Government Living and Dying Well: A National Audit Plan for Palliative and End-of-Life Care in Scotland The Scottish Government Edinburgh September 2008 Disclosure of Interest: F. Chiplen: None Declared, S. Lawton: None Declared, G. Linklater: None Declared, S. Salunke Grant/research support from: Shire Innovation award for registrars, L. Cogdell: None Declared, A. Fraser: None Declared, B. Vijayan: None Declared.